Characteristics of Karst Cave Development in Urban Karst Area and Its Effect on the Stability of Subway Tunnel Construction - Fei Xue; Minjun Cai; Tianzuo Wang; Tongyang Zhao (Advances in Civil Engineering)
The existence of karst caves poses a large threat to safe tunnel construction in a karst area. This paper presents a synthetic method to evaluate the collapse risk before subway tunnel construction with Yang-Jian interval tunnel as a case study. The crosshole seismic Computed Tomography (CT) integrated with Geological Drilling (Geo-D) was first applied to accurately delineate the karst location and its scale. Then, 483 groups of seismic wave CT images were recorded, and 524 karst cave anomalies were found. The height of karst caves in the study area is 1–20 m and mainly concentrated at approximately 5 m. The vertical distance between the karst cave and the tunnel is mainly within 15 m. According to the detection results, a series of numerical models were built and calculated using FLAC3D to investigate the effect of different sizes and locations of karst caves on the displacement and stability of the surrounding rock in tunnels. Afterwards, based on the simulation results, the disturbance degree evaluation index was established to quantitatively evaluate the risk level of karst caves. The evaluation results indicate that the buried depth of the karst cave greatly affects the disturbance degree. No treatment is required for the deeply buried karst cave that is more than 7 m from the tunnel. When the distance between the cave and the tunnel is less than 7 m, there is a critical size of the cave. Karst caves that are larger than that critical value must be filled with a single slurry or binary slurry before tunnel construction to eliminate the risk of tunnel collapse. This study can be used to provide a more efficient and economical program for metro tunnel construction above a karst cave.